Unveiling the electrochemical CO oxidation activity on support-free porous PdM (M = Fe, Co, Ni) foam-like nanocrystals over a wide pH range - Belal Salah (14150460) (2023)
Binary PdM-based nanocrystals are efficient electrocatalysts for a wide range of renewable and green fuel cell applications; however, their poisoning by CO is a great barrier for commercialization, so it is pivotal to solve this issue. Herein, we fabricated support-free PdM alloys (M = Fe, Co, and Ni) by a prompt one-step aqueous-solution co-reduction with sodium borohydride driven by the coalescence growth mechanism. This forms support-free PdM porous foam-like nanostructures with well-defined compositions from the ICP-OES analysis and clean surface without any hazardous chemicals or multiple reaction steps. The as-prepared PdM foam-like nanostructures were demonstrated for carbon monoxide oxidation (COOxid) electrocatalysis at varied electrolyte pH compared with commercial Pd/C catalyst. The foam-like PdFe nanocrystals achieved an excellent electrochemical COOxid activity that was at least 2.18-times of PdCo, 4.35-times of PdNi, and 1.56-times of Pd/C in both alkaline (KOH) and acidic (HClO4) electrolytes, but PdCo was the best in neutral (NaHCO3) medium. The superior activity of PdM is due to the strain and alloying effect, which promoted the superb CO oxidation durability for 1000 cycles than Pd/C catalyst. This study demonstrated the superiority of support-free bimetallic PdM alloys than Pd/C catalyst in all electrolytes, which may open new gates for understanding CO-poisoning in alcohol-based fuel cells. Other Information Published in: Energy Conversion and Management: X License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ecmx.2023.100449